How Interdisciplinary is Interdisciplinary Economics? - Konar, Arup Kanti (Arthshastra Indian Journal of Economics & Research, 2019)
Interdisciplinarity of economics still proliferates. Interdisciplinary colonization can be substituted for simply interdisciplinarity. Interdisciplinarity of economics can be translated or mapped into the fact that economics is colonizing (or imperialising) and being colonised by non-economics disciplines in the name of interdisciplinary economics. Evidence indicates that colonization of economics by non-economics discipline(s) is more powerful than colonization of noneconomics discipline(s) by economics.